Core–shell SiO2‐coated Fe3O4 with a surface molecularly imprinted polymer coating of folic acid and its applicable magnetic solid‐phase extraction prior to determination of folates in tomatoes. Issue 15 (12th July 2016) - Areerob, Yonrapach; Sricharoen, Phitchan; Limchoowong, Nunticha; Chanthai, Saksit
Abstract : A novel core–shell magnetic surface molecularly imprinted polymer with folic acid as a template was successfully synthesized by the sol–gel method. To generate Lewis acid sites in the silica matrix for the interaction of the metal coordinate with the template, 3‐aminopropyltriethoxysilane was used as a functional monomer, tetraethyl orthosilicate as a cross‐linker, and aluminum ions as a dopant. The magnetite encapsulated by the silica shell plays an important role as a magnetic‐coated polymer. The synthesized product was characterized by powder X‐ray diffraction, scanning electron microscopy, transmission electron microscopy, and FTIR and UV/Vis spectroscopy. The powder X‐ray diffraction patterns, FTIR and UV/Vis spectra confirmed the characteristics of the as‐prepared silica coated magnetite and folic acid molecularly imprinted polymer. It was successfully applied for magnetic solid‐phase extraction prior to the determination of folates in tomato samples using high‐performance liquid chromatography with photodiode array detection. The detection limit of the proposed method was 1.67 μg/L, and results were satisfactory, with a relative standard deviation of < 3.94%.